Characterization and comparison of thermostability of purified beta-glucosidases from a mesophilic Aureobasidium pullulans and a thermophilic Thermoascus aurantiacus - Ribeiro Leite, Rodrigo Simoes; Gomes, Eleni; da Silva, Roberto (Elsevier B.V., 2007)
The thermophilic fungus Thermoascus aurantiacus 179-5 and the mesophilic Aureobasidium pullulans ER-16 were cultivated in corn-cob by solid state fermentation for P-glucosidase production. After fermentation both enzymes were purified. The beta-glucosidases produced by the strains A. pullulans and T aurantiacus were most active at pH 4.0-4.5 and 4.5, with apparent optimum temperatures at 80 and 75 degrees C, respectively. Surprisingly, the enzyme produced by the mesophilic A. pullulans was stable over a wider range of pH (4.5-9.5 against 4.5-6.5) and more thermostable (98% after 1 h at 75 degrees C against 98% after 1 h at 70 degrees C) than the enzyme from the thermophilic T. aurantiacus. The t((1/2)) at 80 degrees C were 90 and 30 min for A. pullulans and T. aurantiacus, respectively. beta-Glucosidase thermoinactivation followed first-order kinetics and the energies of denaturation were 414 and 537 kJ mol(-1) for T. aurantiacus and A. pullulans, respectively. The result showed that beta-glucosidase obtained from the mesophilic A. pullulans is more stable than that obtained from the thermophilic T. aurantiacus. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: beta-glucosidase; Aureobasidium pullulans; Thermoascus aurantiacus; thermoinactivation; thermostability; thermophilic